Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Bài 1:
a, \(x^2\) +2\(x\) = 0
\(x.\left(x+2\right)\) = 0
\(\left[{}\begin{matrix}x=0\\x+2=0\end{matrix}\right.\)
\(\left[{}\begin{matrix}x=0\\x=-2\end{matrix}\right.\)
\(x\) \(\in\) {-2; 0}
b, (-2.\(x\)).(-4\(x\)) + 28 = 100
8\(x^2\) + 28 = 100
8\(x^2\) = 100 - 28
8\(x^2\) = 72
\(x^2\) = 72 : 8
\(x^2\) = 9
\(x^2\) = 32
|\(x\)| = 3
\(\left[{}\begin{matrix}x=-3\\x=3\end{matrix}\right.\)
Vậy \(\in\) {-3; 3}
c, 5.\(x\) (-\(x^2\)) + 1 = 6
- 5.\(x^3\) + 1 = 6
5\(x^3\) = 1 - 6
5\(x^3\) = - 5
\(x^3\) = -1
\(x\) = - 1
1.Tìm x,y biết:
a,|x-7|=15
|x-7|=15 hoặc |x-7|=-15
Với |x-7|=15
x=15+7
x=22
Với |x-7|=-15
x=(-15)+7
x=-(15+7)
x=-22
c,-|3x-2|=-1
-|3x|=-(1+2)
-|3x|=-3
x=(-3):(-3)
x=-9
d,|x-4|-(-3)=2016
|x-4|=2016-(-3)
|x-4|=2016-3
|x-4|=2013
|x-4|=2013 hoặc |x-4|=-2013
Với |x-4|=2013
x=2013+4
x=2017
Với|x-4|=-2013
x=(-2013)-4
x=-(2013+4)
x=-2017
2 Tìm x biết :
b,x2+x-6=0
x2+x-6=0
x2+x=0+6
x2+x=6
22+2=6
x=2
a) \(\Rightarrow\orbr{\begin{cases}x-7=15\\x-7=-15\end{cases}\Rightarrow\orbr{\begin{cases}x=22\\x=-8\end{cases}}}\)
KL \(\orbr{\begin{cases}x=22\\x=-8\end{cases}}\)
b) x/4 =12/y=3/4 => x/4=3/4=12/y => 3/4=3/4=12/y => 12/16 =12/16 =12/y => 12/12=12/16=12/16
Vậy x=3 ;y=16
bài 2: (x-3).(y+2) = -5
Vì x, y \(\in\)Z => x-3 \(\in\)Ư(-5) = {5;-5;1;-1}
Ta có bảng:
x-3 | 5 | -5 | -1 | 1 |
y+2 | 1 | -1 | -5 | 5 |
x | 8 | -2 | 2 | 4 |
y | -1 | -3 | -7 | 3 |
bài 3: a(a+2)<0
TH1 : \(\orbr{\begin{cases}a< 0\\a+2>0\end{cases}}\)=>\(\orbr{\begin{cases}a< 0\\a>-2\end{cases}}\)=> -2<a<0 ( TM)
TH2: \(\orbr{\begin{cases}a>0\\a+2< 0\end{cases}}\Rightarrow\orbr{\begin{cases}a>0\\a< -2\end{cases}}\Rightarrow loại\)
Vậy -2<a<0
Bài 5: \(\left(x^2-1\right)\left(x^2-4\right)< 0\)
TH 1 : \(\hept{\begin{cases}x^2-1>0\\x^2-4< 0\end{cases}}\)\(\Rightarrow\hept{\begin{cases}x^2>1\\x^2< 4\end{cases}}\)\(\Rightarrow\hept{\begin{cases}x>1\\x< 2\end{cases}}\)\(\Rightarrow\)1 < a < 2
TH 2: \(\hept{\begin{cases}x^2-1< 0\\x^2-4>0\end{cases}}\)\(\Rightarrow\hept{\begin{cases}x^2< 1\\x^2>4\end{cases}}\)\(\Rightarrow\hept{\begin{cases}x< 1\\x>2\end{cases}}\)\(\Rightarrow\)loại
Vậy 1<a<2
\(\text{ x . (x - 3) = 0}\)
\(\Rightarrow\orbr{\begin{cases}x=0\\x-3=0\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}x=0\\x=3\end{cases}}\)
vậy_______
1 ) 5 - ( 10 - x ) = 7
10 - x = 5 - 7
10 - x = - 2
x = 10 - ( - 2 )
x = 12
Vậy x = 12
a) (x+2)2+(y-3)4 = 0
\(\Rightarrow\hept{\begin{cases}\left(x+2\right)^2=0\\\left(y-3\right)^4=0\end{cases}\Rightarrow\hept{\begin{cases}x=-2\\x=3\end{cases}}}\)
Vậy ...
thanks nha